Integration of Moderation Values in Islamic Education as an Effort to Prevent Radicalism - Madhar Amin (LECTURES: Journal of Islamic and Education Studies, 2024)
The integration of moderation values in Islamic education is an important concern in the context of efforts to prevent radicalism. Education that prioritizes moderation can shape the character of students who are more tolerant, open-minded, and able to appreciate differences. Such education serves as a bulwark against the influence of radical ideologies that often utilize the loopholes of narrow and fanatical religious understanding. This research uses a descriptive qualitative approach. The result of this study is that with a coordinated and comprehensive approach, and the values of moderation can be effectively integrated into the Islamic education curriculum, it can form a more tolerant and inclusive generation, and can contribute to the prevention of radicalism, especially among young people.